(untitled) (Eastern Green Neurosurgery, 2024)
Dyke -Davidoff- Masson (DDM) Syndrome is rare neurological disorder commonly affecting the children but is rarely reported in adults as well. It mostly presents with seizure, hemiparesis followed by mental retardation and facial asymmetry. We here in report a case of 28 years old female (G3P2A0) with 34+ weeks of pregnancy who presented with generalized tonic clonic seizures and was incidentally diagnosed as DDM. She was managed with an External ventricular drain and antiepileptic medication. This case report aims to draw the attention of health care professionals to keep DDM as a differential in a patient with seizure.